Principal's Communication Style and Learning Process Effectiveness during Pandemic: The Case of SMP PGRI 1 Cigombong - Agustina Multi Purnomo; Raisya Nurrachmah (Universitas Kristen Satya Wacana, 2022)
This study examined the principal's communication style in encouraging learning effectiveness during the pandemic in junior high school. Previous studies have not explored the principal's communication style in encouraging the effectiveness of online and limited face-to-face learning during the pandemic. This research used a qualitative case study method. The data collection techniques were interviews with one principal, eleven teachers, three education staff, five students, three parents, observation on the learning process, and document data analysis. This research used the six leadership communication styles approach from Tubbs and Moss. The study found that the principal applied the equalitarian, structuring, dynamic, and relinquishing styles. The learning process was adequate to achieve the score and graduating target. Therefore, the learning effectiveness needed improvement because there needs encouraging student activity, improving the teacher's capacities, and encouraging parent participation in the learning process. The principal's communication styles encouraged overcoming barriers due to the lack of online interaction and limited face-to-face learning but did not directly improve the learning effectiveness problem. The principal's communication styles failed to encourage learning effectiveness because the problem was not only communication. The principal was not arranged a particular assessment to solve the learning effectiveness problem.